Copper-mediated selective aerobic oxidative C3-cyanation of indoles with DMF. Issue 43 (21st October 2015) - Xiao, Jing; Li, Qiang; Chen, Tieqiao; Han, Li-Biao
Graphical abstract: Under an oxygen atmosphere, the copper-mediated direct C3-cyanation of indole C–H bonds, using cheap and safe DMF as a CN source, took place selectively to produce the corresponding C3-cyanoindoles in good yields. A possible mechanism for this selective cyanation was proposed. Abstract: Under an oxygen atmosphere, the copper-mediated direct C3-cyanation of indole C–H bonds, using cheap and safe DMF as a CN source, took place selectively to produce the corresponding C3-cyanoindoles in good yields. A possible mechanism for this selective cyanation was proposed.